2015
DOI: 10.1002/ijop.12196
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trajectories of bicultural identity integration in recently immigrated Hispanic adolescents: Links with mental health and family functioning

Abstract: This study examined, in a sample of recently immigrated Hispanic adolescents in Miami and Los Angeles, the extent to which bicultural identity integration (BII; involving the ability to synthesise one's heritage and receiving cultural streams and to identify as a member of both cultures) is best understood as a developmental construct that changes over time or as an individual-difference construct that is largely stable over time. We were also interested in the extent to which these trajectories predicted ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 28 publications
8
107
1
1
Order By: Relevance
“…These effects were detected above and beyond the influence of demographic characteristics and personality factors like neuroticism levels. More recently, Schwartz et al (2015) explored the longitudinal association between BII and levels of psychological adjustment and family functioning in 9th grade Hispanic adolescents that had recently migrated to the United States. Data on BII levels was gathered across five different time points for the adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects were detected above and beyond the influence of demographic characteristics and personality factors like neuroticism levels. More recently, Schwartz et al (2015) explored the longitudinal association between BII and levels of psychological adjustment and family functioning in 9th grade Hispanic adolescents that had recently migrated to the United States. Data on BII levels was gathered across five different time points for the adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The authors report that two trends were detected across the 5 initial time points: high and low levels of BII. At the sixth time of measurement, the adolescents with high levels of BII also tended to show higher levels of self-esteem, optimism, and more fulfilling family relationships, compared to those lower in BII (Schwartz et al, 2015). Hence, there is support for the idea that a salient and strong bicultural identity might signal full integration of this identity within the self.…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the Institutional Review Boards at the University of Miami and the University of Southern California, and by the Research Review Committees at each of the respective participating school districts. Additional study details are reported in Schwartz et al (2012, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Given that, relative to their parents, adolescents are often provided more opportunities to integrate into U.S. culture (e.g., English speaking peers and American school system), they Americanize at levels that far outpace their parents. These parent-adolescent acculturation discrepancies have been associated with family functioning (Schwartz et al, 2015; Unger et al, 2009). For example, researchers have found that larger parent–adolescent Hispanicism discrepancies, defined as the difference between parents' and adolescents' orientation toward Hispanic cultural practices (e.g., comfort and use of language and traditions), were significantly related to lower adolescent reports of family functioning (Córdova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, immigrant and minority members also may develop strategies that help them in dealing with these demands. One such strategy is described in the research of Schwartz et al (). In their six‐wave longitudinal study, these authors followed first‐generation adolescent immigrants with a Latino background and could identify two groups.…”
Section: Contextual Variations In Immigrant Adaptationmentioning
confidence: 99%